Constitutional Court of the Republic of Kazakhstan: continuity and innovation - Abaideldinov, Y. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
The article discusses some decisions of the Constitutional Council of the Republic of Kazakhstan on a number of issues of constitutional and international law. These legal positions, as a continuity, in accordance with paragraph 1 of Article 66 of the CLRK «On the Constitutional Court of the Republic of Kazakhstan», can establish the basis for the forthcoming activities of the recreated Constitutional Court of the Republic of Kazakhstan. The article emphasizes that constitutionality in the country will be ensured not only by the Constitutional Court, but also by all branches of the unified state power, every state body, and every civil servant throughout the country. The attention is drawn to the concept of «presumption of constitutionality» of acts of state bodies: laws; decisions of judicial and executive bodies.